Genotypic study of Citrobacter koseri, an emergent platelet contaminant since 2012 in France. Issue 2 (5th December 2019) - Emery, Audrey; Marpaux, Nadine; Naegelen, Christian; Valot, Benoît; Morel, Pascal; Hocquet, Didier
Abstract : BACKGROUND: Transfusion‐transmitted bacterial infection is a rare occurrence but the most feared complication in transfusion practices. Between 2012 and 2017, five cases of platelet concentrates (PCs) contaminated with the bacterial pathogen Citrobacter koseri (PC‐ Ck ) have been reported in France, with two leading to the death of the recipients. We tested the possibilities of the emergence of a PC‐specific clone of C. koseri ( Ck ) and of specific bacterial genes associated with PC contamination. STUDY DESIGN AND METHODS: The phylogenetic network, based on a homemade Ck core genome scheme, inferred from the genomes of 20 worldwide Ck isolates unrelated to PC contamination taken as controls (U‐ Ck ) and the genomes of the five PC‐ Ck, explored the clonal relationship between the genomes and evaluated the distribution of PC‐ Ck throughout the species. Along with this core genome multilocus sequence typing approach, a Ck pan genome has been used to seek genes specific to PC‐ Ck isolates. RESULTS: Our genomic approach suggested that the population of C. koseri is nonclonal, although it also identified a cluster containing three PC‐ Ck and eight U‐ Ck . Indeed, the PC‐ Ck did not share any specific genes. CONCLUSION: The elevated incidence of PCs contaminated by C. koseri in France between 2012 and 2017 was not due to the dissemination of a clone. The determinants of the recent outbreaks of PC contamination with C. koseri are still unknown.